Pengaruh Peningkatan Pajak Restoran Terhadap Pendapatan Asli Daerah di Kota Jayapura Tahun 2016-2025 - Maylan Adventesia Manullang; Julius Ary Mollet; Maria Kbarek (Jurnal Kajian Ekonomi dan Studi Pembangunan, 2026)
This study aims to analyze the development of restaurant tax realization, examine its effect on Local Own-Source Revenue (PAD), and identify supporting and inhibiting factors for optimizing restaurant tax collection in Jayapura City for the 2016-2025 period. The research employed a mixed method, with quantitative analysis using simple linear regression on secondary data of restaurant tax and PAD realizations from BAPENDA Jayapura City, as well as qualitative analysis through interviews with key informants. The results show that restaurant tax realization fluctuated, increasing before the pandemic (2016-2019), drastically declining in 2020 due to COVID-19, recovering strongly in 2021-2022 with a peak of IDR 65.03 billion, then decreasing again in 2023-2025. Restaurant tax has a positive and significant effect on PAD with a correlation coefficient (R) of 0.907 (very strong), a coefficient of determination (R²) of 82.3 percent, and a regression equation of PAD = 13.80 billion + 4.482 (Restaurant Tax), indicating a multiplier effect. Supporting factors include a strong legal foundation, significant economic potential, information technology, and a self-assessment system, while inhibiting factors include fluctuations in the number of taxpayers, data gaps, low compliance, limited human resources, and external factors such as pandemics and inflation. Keywords: Restaurant Tax, Local Own-Source Revenue (PAD)